Performance of e-ASPECTS software in comparison to that of stroke physicians on assessing CT scans of acute ischemic stroke patients - Herweh, Christian; Ringleb, Peter A.; Rauch, Geraldine; Behrens, Lars; Möhlenbruch, Markus Alfred; Gottorf, Rebecca Barbara; Richter, Daniel; Schieber, Simon; Nagel, Simon (International journal of stroke, 2016)
BackgroundThe Alberta Stroke Program Early CT score (ASPECTS) is an established 10-point quantitative topographic computed tomography scan score to assess early ischemic changes. We compared the performance of the e-ASPECTS software with those of stroke physicians at different professional levels.MethodsThe baseline computed tomography scans of acute stroke patients, in whom computed tomography and diffusion-weighted imaging scans were obtained less than two hours apart, were retrospectively scored by e-ASPECTS as well as by three stroke experts and three neurology trainees blinded to any clinical information. The ground truth was defined as the ASPECTS on diffusion-weighted imaging scored by another two non-blinded independent experts on consensus basis. Sensitivity and specificity in an ASPECTS region-based and an ASPECTS score-based analysis as well as receiver-operating characteristic curves, Bland?Altman plots with mean score error, and Matthews correlation coefficients were calculated. Comparisons were made between the human scorers and e-ASPECTS with diffusion-weighted imaging being the ground truth. Two methods for clustered data were used to estimate sensitivity and specificity in the region-based analysis.ResultsIn total, 34 patients were included and 680 (34???20) ASPECTS regions were scored. Mean time from onset to computed tomography was 172?±?135?min and mean time difference between computed tomographyand magnetic resonance imaging was 41?±?31?min. The region-based sensitivity (46.46% [CI: 30.8;62.1]) of e-ASPECTS was better than three trainees and one expert (p?≤?0.01) and not statistically different from another two experts. Specificity (94.15% [CI: 91.7;96.6]) was lower than one expert and one trainee (p?
Gesehen am 06.09.2019